2016
DOI: 10.1146/annurev-animal-021815-111216
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives from the Avian Phylogenomics Project: Questions that Can Be Answered with Sequencing All Genomes of a Vertebrate Class

Abstract: The rapid pace of advances in genome technology, with concomitant reductions in cost, makes it feasible that one day in our lifetime we will have available extant genomes of entire classes of species, including vertebrates. I recently helped cocoordinate the large-scale Avian Phylogenomics Project, which collected and sequenced genomes of 48 bird species representing most currently classified orders to address a range of questions in phylogenomics and comparative genomics. The consortium was able to answer que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 79 publications
1
50
0
Order By: Relevance
“…In this review, we focus on the final step in this methodological progress: genomic data, which has become standard practise in ornithology (Kraus and Wink 2015;Jarvis 2016;Oyler-McCance et al 2016;Toews et al 2016). Following Toews et al (2016), we consider the following next generation sequencing techniques as genomic tools: genome sequencing and resequencing, reduced representation techniques (genotype-bysequencing [GBS] and restriction-site-associated DNA sequencing [RADseq]), sequence capture and RNA sequencing.…”
Section: Open Accessmentioning
confidence: 99%
“…In this review, we focus on the final step in this methodological progress: genomic data, which has become standard practise in ornithology (Kraus and Wink 2015;Jarvis 2016;Oyler-McCance et al 2016;Toews et al 2016). Following Toews et al (2016), we consider the following next generation sequencing techniques as genomic tools: genome sequencing and resequencing, reduced representation techniques (genotype-bysequencing [GBS] and restriction-site-associated DNA sequencing [RADseq]), sequence capture and RNA sequencing.…”
Section: Open Accessmentioning
confidence: 99%
“…Future research into avian hybrid zones and introgression is expected to rely on genomic data (Toews et al, 2016, Kraus and Wink, 2015, Jarvis, 2016. Whole-genome sequences will provide detailed information about patterns of divergence between hybridizing and diverging taxa and about patterns of variation across hybrid zones (Harrison and Larson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Genomics has become a standard practise, also in ornithology (Toews et al, 2016, Kraus andWink, 2015), opening avenues to answer longstanding questions in speciation and hybridization (Jarvis, 2016, Seehausen et al, 2014. Studies in speciation and hybridization genomics revealed that levels of genetic differentiation between species can be highly variable across the genome: genetic differentiation accumulates in certain genomic regions, while divergence is hampered in other regions by homogenizing gene flow, resulting in a heterogeneous genomic landscape (Nosil et al, 2009, Nosil and Feder, 2012b, Harrison and Larson, 2016.…”
Section: Reinforcement Speciation Reversal Hybrid Speciation Stable Hmentioning
confidence: 99%
See 2 more Smart Citations